HIV persistence in lymph nodes. Issue 4 (July 2021) - Banga, Riddhima; Munoz, Olivia; Perreau, Matthieu
Abstract : Purpose of review: HIV persists in distinct cellular and anatomical compartments in the body including blood, Central nervous system, and lymphoid tissues (spleen, lymph nodes [LNs], gut-associated lymphoid tissue) by diverse mechanisms despite antiretroviral therapy. Within LNs, human and animal studies have highlighted that a specific CD4 T cell subset - called T follicular helper cells locating in B cell follicles is enriched in cells containing replication-competent HIV as compared to extra-follicular CD4 T cells. Therefore, the objective of the present review is to focus on the potential mechanisms allowing HIV to persist within LN microenvironment. Recent findings: The combination of factors that might be involved in the regulation of HIV persistence within LNs remain to be fully identified but may include - the level of activation, antiretroviral drug concentrations, presence of cytolytic mechanisms and/or regulatory cells, in addition to cell survival and proliferation propensity which would ultimately determine the fate of HIV-infected cells within LN tissue areas. Summary: HIV persistence in blood and distinct body compartments despite long-standing and potent therapy is one of the major barriers to a cure. Given that the HIV reservoir is established early and is highly complex based on composition, viral diversity, distribution, replication competence, migration dynamics across the human body and possible compartmentalization in specific tissues, combinatorial therapeutic approaches are needed that may synergize to target multiple viral reservoirs to achieve a cure for HIV infection.